2016
DOI: 10.1111/ijcs.12318
|View full text |Cite
|
Sign up to set email alerts
|

Financial literacy and savings decisions by adult financial consumers in Zimbabwe

Abstract: We use survey data from a sample of 4000 adult financial consumers in Zimbabwe to analyse the determinants of financial literacy and its effect on individual's savings decisions. Results show that women have lower financial literacy than men. Furthermore, individuals' residing in rural areas exhibit lower financial literacy compared with urban financial consumers. Financial literacy and financial services interventions targeting women and rural individuals should be strengthened. Econometric results show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
82
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(107 citation statements)
references
References 38 publications
20
82
1
4
Order By: Relevance
“…Even though our study is not free of limitations, it still captures a specific mix of financial literacy and financial behaviour of low‐income consumers from rural regions of Poland. Furthermore, consistent with the results reported by Baumann and Hall (), Alsemgeest (), and Murendo and Mutsonziwa (), our results showed that the incorporation of the financial inclusion variable in the financial capability index helped us to capture the specific mix of financial literacy and behaviour of low‐income consumers from rural regions of Poland. Future research needs to further examine the financial and poverty characteristics and how these factors affect the financial capability index variables of low‐income consumers from rural regions.…”
Section: Limitations and Future Researchsupporting
confidence: 91%
See 4 more Smart Citations
“…Even though our study is not free of limitations, it still captures a specific mix of financial literacy and financial behaviour of low‐income consumers from rural regions of Poland. Furthermore, consistent with the results reported by Baumann and Hall (), Alsemgeest (), and Murendo and Mutsonziwa (), our results showed that the incorporation of the financial inclusion variable in the financial capability index helped us to capture the specific mix of financial literacy and behaviour of low‐income consumers from rural regions of Poland. Future research needs to further examine the financial and poverty characteristics and how these factors affect the financial capability index variables of low‐income consumers from rural regions.…”
Section: Limitations and Future Researchsupporting
confidence: 91%
“…Second, correlation and OLS regression analyses showed that financial inclusion is an integral and one of the most important variables next to desirable financial behaviour in Xiao’s financial capability index, supporting H2 (Atkinson et al, ; Murendo & Mutsonziwa, ; Nicolini et al, ). Thus, our results confirmed a previous study by Kempson et al (, p. 8) who stated that “external factors that can affect how the internal capacity manifests itself into actual behaviours include financial resources, social norms and obligations, financial infrastructure, and existing financial consumer protection mechanisms”.…”
Section: Summary and Discussionmentioning
confidence: 73%
See 3 more Smart Citations